Estudo fitoquímico e avaliação da potencialidade farmacológica de extratos de crateva benthamii (capparaceae) - Pereira Junior , Raimundo Carlos (2005)
Crateva benthamii (Capparaceae), a common tree species in the Amazonian floodplain areas, may reach from 6 to 12 m in height. There are reports on it being used by the people inhabiting the riverside, on account of its bark being used as antiseptic and against snake poison, its roots and leaves being used as tonics for stomachic problems and its topical use as auxiliaries in the recovery of the rheumatism. Aiming to evaluate the pharmacological and biotechnological potentialities of the C. benthamii extracts, the present study reports on the findings obtained on the evaluation of the methanol/water extract (80:20) of the C. benthamii bark, on the antifungal tests against the xylophagous fungus Pycnoporus sanguineus and on the methanol/water (80:20) and dichloromethane extracts of the bark on the antibacterial tests against species Staphylococus aureus, Escherichia coli , Salmonella london ,Shigella sonni, Shigella paratyphi , Shigella tryphimurium, as well as the characterization of the substances that compose the essential oil extracted of its leaves. The methanol/water extract (80:20) on the antibacterial assays showed to be active to Staphylococus aureus bacterium species on 1.20 mg/mL concentration both by plate cavity diffusion (CP) as plate discus (DP) method, while the dichloromethane extract did not show activity for others bacteria studied. On the assay to evaluate the antifungal extract activity against P. sanguineus the methanol/water extract on the concentration of 0,1 g/mL showed moderate inhibitor activity on micelial growth. Statistical data showed that the concentration increase may inhibit micelial growth. The 13C NMR spectrum analyses of the dichloromethane extract showed Lupeol and Germanicol as majority triterpenes. Chromatographic fraction resulted on the Lupeol isolation and identification in addition to another not identified substance similar to yellowish-coloured oil, with a pleasant odour, whose 13C NMR spectrum suggests being a -amirin ester. In the essential oil CG/EM analysis eight substances were identified, with the trans-caryophyllene being one of the major compounds.